Submucosal Injection Solution for Endoscopic Resection in Gastrointestinal Tract: A Traditional and Network Meta-Analysis - Zhang Yu Huai; Wei Feng Xian; Luo Chang Jiang; Wang Xi Chen (Gastroenterology Research and Practice)
Objective. To explore and define the current optimal submucosal injection solution used in ESD and EMR for gastrointestinal tract neoplasms in terms of clinical outcomes and other aspects. Methods. PubMed, Cochrane Library, Embase, and clinical trials register center were searched with terms of “endoscopic resection” and “submucosal injection solution” to identify relevant randomized controlled trials (RCTs). Both direct comparison using traditional meta-analysis method and indirect comparison using network meta-analysis method were performed. Results. A total of 11 RCTs with 1152 patients were included. Meta-analysis showed that, compared with normal saline, other submucosal injection solutions induced a significant increase in terms of en bloc resection rate (I2=0%, OR = 2.11, 95% CI (1.36, 3.26), and P= 0.008) and complete resection rate (I2=0%, OR = 2.14, 95% CI (1.41, 3.24), and P= 0.0003); and there was no significant difference in the incidence of total complications (I2=0%, OR = 0.87, 95% CI (0.59, 1.29), and P= 0.49). Conclusions. Other newly developed submucosal injection solutions significantly increased en bloc resection rate and complete resection rate and decreased bleeding rate and finical cost of endoscopic resection in gastrointestinal tract, while current evidence did not find the difference between them, which need to be explored by further studies.